Etnobotani Tumbuhan Liar sebagai Sumber Pangan di Dusun Serundung Permai, Kabupaten Melawi - Hanifa Hanifa; Syamswisna Syamswisna; Hayatul Fajri (Jurnal Ilmu Kehutanan, 2026)
Ethnobotany examines the relationships between local ethnic communities and the environment, including the use of plants to meet daily needs. Therefore, this research aimed to identify the species of wild plants used as food sources by the community in Serundung Permai I Hamlet, Melawi Regency, West Kalimantan Province. Data collection techniques used data triangulation, namely interviews, observation, and documentation, while snowball sampling determined the number of informants to be 20. The results showed that the community of Serundung Permai I Hamlet used 32 wild plant species as food sources, including vegetables (23 species), spices (5 species), and fruits (4 species). This indicates that many wild plants still have the potential to be used as food sources or alternatives. However, knowledge about the availability and use of wild plants as food sources has gradually declined, which may threaten continued use and conservation. The documented wild plants used by the community of Serundung Permai I Hamlet became part of a conservation effort of useful wild plant species.